2018
DOI: 10.1038/s41467-018-07129-6
|View full text |Cite
|
Sign up to set email alerts
|

Locally anchoring enzymes to tissues via extracellular glycan recognition

Abstract: Success of enzymes as drugs requires that they persist within target tissues over therapeutically effective time frames. Here we report a general strategy to anchor enzymes at injection sites via fusion to galectin-3 (G3), a carbohydrate-binding protein. Fusing G3 to luciferase extended bioluminescence in subcutaneous tissue to ~7 days, whereas unmodified luciferase was undetectable within hours. Engineering G3-luciferase fusions to self-assemble into a trimeric architecture extended bioluminescence in subcuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 64 publications
(80 reference statements)
2
49
0
Order By: Relevance
“…Here, we used a combination of annexin V staining of phosphatidylserine and a membrane-impermeable DNA-binding dye (LIVE/DEAD R , Invitrogen) to quantify Jurkat T cell death induced by G1/G3 Zipper, G1, or G3 as a function of galectin concentration and time. Note, cells were treated with as low as 0.5 µM G1/G3 Zipper in all experiments based on a prior report showing that high concentration of this protein led to loss of cell integrity (Fettis et al, 2019), whereas cells were treated with as high as 5 µM G1 or G3 based on the reported effective dose of these proteins (Restuccia et al, 2015(Restuccia et al, , 2018Farhadi et al, 2018;Fettis and Hudalla, 2018;Fettis et al, 2019). For each concentration of galectin (0.5, 1, 2.5, and 5 µM) tested, G1/G3 Zipper induced significantly more cell death by 24 h than an equimolar combination of G1 and G3 (Figure 2A).…”
Section: G1/g3 Zipper Induces Jurkat T Cell Death More Potently Than mentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we used a combination of annexin V staining of phosphatidylserine and a membrane-impermeable DNA-binding dye (LIVE/DEAD R , Invitrogen) to quantify Jurkat T cell death induced by G1/G3 Zipper, G1, or G3 as a function of galectin concentration and time. Note, cells were treated with as low as 0.5 µM G1/G3 Zipper in all experiments based on a prior report showing that high concentration of this protein led to loss of cell integrity (Fettis et al, 2019), whereas cells were treated with as high as 5 µM G1 or G3 based on the reported effective dose of these proteins (Restuccia et al, 2015(Restuccia et al, , 2018Farhadi et al, 2018;Fettis and Hudalla, 2018;Fettis et al, 2019). For each concentration of galectin (0.5, 1, 2.5, and 5 µM) tested, G1/G3 Zipper induced significantly more cell death by 24 h than an equimolar combination of G1 and G3 (Figure 2A).…”
Section: G1/g3 Zipper Induces Jurkat T Cell Death More Potently Than mentioning
confidence: 99%
“…First, G1 fixed in a homodimeric configuration has increased pro-apoptotic signaling activity when compared to native G1, regardless of whether the dimeric structure is established by a peptide linker, α-helical coiled-coil, Fc fusion, or synthetic polymer (van der Leij et al, 2007;Cedeno-Laurent et al, 2010;Earl et al, 2011;Farhadi and Hudalla, 2016;Fettis and Hudalla, 2018). Second, a synthetic homotrimer of G3 lacked signaling activity when compared to native G3 (Farhadi et al, 2018), likely because its carbohydrate-recognition domain valency was insufficient to activate intracellular signaling pathways to a measurable extent.…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembling peptides can also be used to organize proteins into other nano-scale architectures in addition to nanofibers and nanovesicles. For example, Hudalla and colleagues created nanoassemblies by fusing an enzyme to Galectin-3 via a peptide that forms an α-helical coiled-coil [115] (Figure 12a). Galectin-3 is a protein that binds carbohydrates found on the cell surface and within the extracellular matrix of mammalian tissues, including N -acetyllactosamine and related variants, as well as chondroitin and heparan sulfate glycosaminoglycans [116,117].…”
Section: Moving Beyond Peptides As the Functional Ligandmentioning
confidence: 99%
“…( d ) Bright-field micrographs of Jurkat T cells incubated with PBS (untreated, negative control), wild-type Galectin-3 (WT-G3) (positive control), NL-G3, or NL-TT-G3 for 4 h, which demonstrated that monomeric fusion proteins and trimeric nanoassemblies lacked the activity for inducing T-cell apoptosis that is characteristic of WT-G3. Adapted with permission from reference [115] under Creative Commons Attribution 4.0 International license. Copyright 2018.…”
Section: Figurementioning
confidence: 99%
“…Gal-3 is expressed by many types of human cells including epithelial and immune cells, and also shows a wide sub-cellular distribution [10]. This wide distribution of Gal-3 and its interactions with multiple protein-linked glycans underlie its reported involvement in various cellular processes such as cell differentiation, cell growth, cell apoptosis, cell adhesion, cell cycle regulation, cell migration, immune activation, angiogenesis and chemoattraction [11].…”
Section: Introductionmentioning
confidence: 99%